The Role of Matrix Metalloproteinase2 (MMP2) in Serum and Peritoneal Fluid of Endometriotic Patients - NurIedil Baharuddin; Nusratuddin Abdullah; Telly Tessy; St Maisuri T Chalid; St Maisuri T Chalid (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To determine the role of matrix metalloproteinase-2 (MMP-2) in serum and peritoneal fluid of endometriotic patients. Methods: Research’s design using cross-sectional method in Dr. Wahidin Sudirohusodo hospital and several other hospitals in Makassar within May 2015 until May 2016. Subjects were chosen using consecutive sampling technique. The examination using the ELISA method. The data were analysed using Fisher exact, t-independent, Mann-Whitney, and Spearman association. Results: A total of 50 subjects were recruited in this study. Mostly the value of MMP-2 serum and peritoneal fluid in endometriosis group was higher compare to study control. There was significant different between the total of MMP-2 serum and peritoneal fluid. There was also a significant association between the value of MMP-2 serum and peritoneal fluid with endometriosis. Conclusion: The value of MMP-2 serum and peritoneal fluid were higher in endometriotic patients compared to those without endometriosis. The higher the value of MMP-2 serum and peritoneal fluid, the higher the stage of endometriosis. [Indones J Obstet Gynecol 2018; 6-2: 104-109] Keywords: endometriosis, matrix metalloproteinase-2, MMP-2